Antioxidant activity and potential of Caesalpinia sappan aqueous extract on synthesis of silver nanoparticles - Temsiri Suwan (2018)
The aim of this study was to investigate the antioxidant activity of Caesalpinia sappan aqueous extract (CE) and its potential on synthesis of silver nanoparticles (AgNPs). The antioxidant activity of CE was investigated using ferric reducing antioxidant power (FRAP) assay and two radical scavenging methods using 2,20-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) as free radicals. Silver nitrate (AgNO3) was used as precursor for the synthesis of AgNPs. Effects of AgNO3 concentration, reaction temperature, and duration of reaction were investigated. The obtained AgNPs was characterized using UV-Vis and photon correlation spectrophotometers. The antimicrobial activity of AgNPs was studied by means of diffusion method. The results from FRAP demonstrated that CE had high reducing property of 78.7 ± 2.4 mM Fe2+/mg. The trolox equivalent antioxidant capacity of CE determined by ABTS was 64.8 ± 4.2 µM/mg. The concentration of CE that can inhibit 50% of DPPH radicals (IC50) was 51.2 ± 3.2 µM. These results indicated that CE possesses strong antioxidant and reducing activities. The present study also showed that CE can act as reducing agent to produce AgNPs. The concentration of AgNO3, reaction temperature, and reaction time play an important role on the particles size and zeta potential of the obtained AgNPs. The antimicrobial activity of the AgNPs against Escherichia coli, Candida albicans, and Streptococcus mutants was stronger than against Staphylococcus aureus.